New insights into the archives of redox conditions in seep carbonates from the northern South China Sea - Liang, Qianyong; Huang, Huiwen; Sun, Yuedong; Gong, Shanggui; Wang, Xudong; Xiao, Xi; Dong, Yifei; Feng, Junxi; Feng, Dong (Frontiers in Marine Science, 2022)
Modern cold seeps are of fluctuant flux, which could result in variabilities of geochemical archives through intensively influencing the redox condition in pore fluids. However, the geochemical archives are not fully understood when the redox condition changes. Here, tubular carbonates from the Shenhu Sea Area were used to reconstruct the formation environment and redox conditions. The moderately negative δ13C values of the carbonates (−40.1‰ to −30.8‰, VPDB) indicate a mixed carbon source of thermogenic and biogenic methane. The low δ18O values (−2.7‰ to 1.0‰, VPDB) suggest a type of 18O-depleted pore fluid possibly influenced by gas hydrate formation. Co-variation of MoEF, WEF, CoEF, and CrEF suggests that high Fe contents in the rims of samples R1 and R2 are induced by Fe (oxyhydr)oxidation enrichment, while the positive correlation between MoEF and Mn/Al ratio indicates that high Mn contents in the rims of samples R3 and R4 are induced by Mn (oxyhydr)oxidation enrichment. The occurrence of Fe or Mn enrichment in the rims and the absence of Fe/Mn enrichment in the cores suggest Fe/Mn (oxyhydr)oxides forming in pore fluid rather than in bottom seawater. The carbonate phases of the rims enriched in Fe (oxyhydr)oxides are dominated by high magnesium calcite, while those of the rims enriched in Mn (oxyhydr)oxides are dominated by aragonite. The occurrence of Fe or Mn (oxyhydr)oxides corresponds to the previously proposed formation depth for the carbonate phase. The occurrence of dissolution textures in these rims indicates episodic oxic conditions, which would facilitate Fe2+/Mn2+ oxidation. We suppose that the Fe2+ and Mn2+ could be supplied through fluid seepage or diffusion from underlying sediments when the flux decreased. Similar archives may be applied to qualitatively reflect the changes of redox conditions in seep systems. Similar scenarios may help us understand the geochemical records in seeps of fluctuant flux.